Challenging Autopsy Finding in a Patient With Systemic Sclerosis With CREST Syndrome. (21st September 2018) - Al Agha, Abdel raof; Varshney, Neha; Moussa, Zeinab; Anandan, Vasuki
Abstract: Systemic sclerosis (SS) is a diffuse progressive autoimmune disorder characterized by fibrosis of skin and visceral organs. The SS is a complex autoimmune disease that triggers the immune system to produce autoantibodies and autoimmunity, and initiates fibroblast vasculopathy of blood vessels. The SS causes tightening of skin and developing of vascular and fibrotic changes of internal organs. The etiology of the SS remains unknown. The association of SS with CREST syndrome (ie, calcinosis cutis, Raynaud phenomenon, esophageal dysfunction, sclerodactyly, and telangiectasia) indicates a significantly worse prognosis and poor response to treatment. Pulmonary manifestation is the leading cause of death in patients with SS. Interstitial lung disease (ILD) and pulmonary arterial hypertension (PAH) are the two direct manifestations in scleroderma patients. Aspiration pneumonitis manifests secondary to esophageal dysmotility. The most common pattern of interstitial fibrosis is nonspecific interstitial pneumonia (NSIP) and less common is usual interstitial pneumonia (UIP). PAH, secondary to vascular changes, may lead to various degrees of luminal occlusion, independent of the degree of interstitial fibrosis. We report an autopsy case of a 74-year-old woman with clinical history of primary systemic sclerosis highlighting major pulmonary complications. The patient showed pathognomonic CREST histopathology of lung and esophagus. Sections from esophagus thinning of internal muscularis interna explained the dysmotility symptoms of the patient. In addition, sections from lung showed severe interstitial fibrosis suggestive of UIP pattern of fibrosis. Focal cholesterol granulomas and multinucleated giant cells with foreign material suggested resolving aspiration pneumonitis. Prominent vascular changes such as medial smooth muscle hypertrophy, intimal thickening, and arteriolar narrowing were consistent with PAH. We believe that the constellations of histological changes of lung represent a pulmonary manifestation of systemic sclerosis. Patients with the UIP pattern had a trend toward shorter survival time. Because lung fibrosis is irreversible, early diagnosis is vital to reduce morbidity and mortality.